Inflammation mediates the effect of histidine on a lower risk of colorectal cancer - He, Chunlei; Yang, Yudan; Chen, Shuhui; Liu, Bin; Guo, Jing; Ye, Ding; Sun, Xiaohui; Mao, Yingying; Li, Jiayu (Frontiers in Nutrition, 2026)
BackgroundWhether anti-inflammatory mechanisms mediate the protective effects of histidine against colorectal carcinogenesis remains unexplored. We aimed to assess the association between plasma histidine and colorectal cancer (CRC) and to evaluate the potential mediating role of inflammation.MethodsWe conducted a prospective cohort study using data from the UK Biobank. A total of 261,082 cancer-free participants with plasma histidine data were included. Histidine concentrations were quantified using a nuclear magnetic resonance-based metabolic profiling platform. Incident CRC cases were identified through linkage to cancer registries. Cox proportional hazards regression models were used to assess the association between plasma histidine and CRC risk. Mediation analysis was performed using a regression-based approach with closed-form parameterization and delta method inference.ResultsAfter a median follow-up of 13.3 years, 3,436 incident CRC cases were identified. An inverse association between plasma histidine and CRC risk was observed [Tertile 2 (T2) vs. T1: HR = 0.885; 95% CI = 0.816, 0.960; P = 0.003; T3 vs. T1: HR = 0.890; 95% CI = 0.820, 0.966; P = 0.005]. Mediation analysis identified neutrophils, leukocytes, and C-reactive protein (CRP) as significant mediators. CRP exhibited the largest mediation proportion (14.141%), followed by neutrophils (11.258%) and leukocytes (6.770%).ConclusionsHigher histidine levels are associated with a lower risk of CRC, and systemic inflammation mediates this association. These findings suggest that dietary interventions targeting histidine intake could offer a promising strategy for CRC prevention and burden reduction.